(untitled) (Discourse of Law and Administration, 2025)
Pursuant to Article 42(2) of the Constitution of the Republic of Poland, the right to defence is guaranteed to everyone against whom criminal proceedings are conducted, at every stage thereof. An essential component of the right to defence is also the remain silent, which is granted to everyone from the first procedural act where suspicion of committing a crime arises. However, it turns out that these rules are not clearly articulated in Polish criminal procedure. There is no explicitly formulated obligation to provide information on the right to remain silent, especially for individuals detained without formal charges. This, therefore, raises doubts that require consideration of possible directions of changes towards respecting the right to not have an obligation to self-incriminate.